2016
DOI: 10.1016/j.jcp.2016.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Frozen Gaussian approximation based domain decomposition methods for the linear Schrödinger equation beyond the semi-classical regime

Abstract: The paper is devoted to develop efficient domain decomposition methods for the linear Schrödinger equation beyond the semiclassical regime, which does not carry a small enough rescaled Planck constant for asymptotic methods (e.g. geometric optics) to produce a good accuracy, but which is too computationally expensive if direct methods (e.g. finite difference) are applied. This belongs to the category of computing middlefrequency wave propagation, where neither asymptotic nor direct methods can be directly used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…It is shown that these algorithms are fast and robust for complex linear problems. In [27], domain decomposition methods have been developed and combined with geometric optics and frozen gaussian approximation for computing the solution to the linear Schrödinger equations under and beyond the semi-classical regime. Finally, [9] is dedicated to the development of high-order transmission conditions for SWR methods applied to the Schrödinger equation, using only local operators.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that these algorithms are fast and robust for complex linear problems. In [27], domain decomposition methods have been developed and combined with geometric optics and frozen gaussian approximation for computing the solution to the linear Schrödinger equations under and beyond the semi-classical regime. Finally, [9] is dedicated to the development of high-order transmission conditions for SWR methods applied to the Schrödinger equation, using only local operators.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of the method shows that it can lead to fast and robust algorithms for complex linear problems. In [35], domain decomposition methods have been developed when using geometric optics and frozen gaussian approximations for computing the solution to linear Schrödinger equations under and beyond the semi-classical regime.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of the method shows that it can lead to fast and robust algorithms for complex linear problems. In [33], domain decomposition methods have been developed when using geometric optics and frozen gaussian approximation for computing the solution to linear Schrödinger equations beyond the semi-classical regime.…”
Section: Introductionmentioning
confidence: 99%